On Elephants and Matters Epistemological: Reply to Etzel Cardeña’s Guest Editorial "On Wolverines and Epistemological Totalitarianism" - Grossman, Neal (Journal of Scientific Exploration, 2011)
<!–[if gte mso 9]> Normal 0 MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; –> <!–[endif] –> The Guest Editorial On Wolverines and Epistemological Totalitarianism by Etzel Cardeña (JSE 24(3), Fall 2011) is little more than a rant, in which invective, ridicule, and mockery take the place of reasoned argumentation. Mind you, there’s nothing wrong with a good rant, especially when one agrees with the overall perspective, and I actually found myself in agreement with much of what the author had to say. Most of Cardeña’s anger is directed at those Materialist philosophers and psychologists who happily pontificate against the possibility of psi while remaining studiously ignorant of the data that parapsychological research has uncovered. I think everyone who comes to parapsychology with an open mind at some point experiences the same frustration that Cardeña expresses toward Materialist idealogues, whose conclusions and opinions have been formed a priori and appear to be impervious to empirical data. But he seems equally upset with those who are “pro-psi,” lamenting "the epistemological absolutism that pervades both the strident anti-psi and pro-psi proponents from what I consider a healthy abeyance from fully committing to a closed position in science or in other aspects of life." (Cardeña, p. 539)